2007
DOI: 10.1111/j.1365-3040.2007.01753.x
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of stromal Pi induces high ‘energy‐dependent’ antenna exciton quenching (qE) by decreasing proton conductivity at CFO‐CF1 ATP synthase

Abstract: This work tests two models to account for the effects of depletion of stromal inorganic phosphate (Pi), which results in down-regulation of light capture via the exciton quenching (qE) mechanism and has been proposed to act in feedback regulation of the light reactions. In both models, antenna down-regulation is activated by acidification of the lumen, despite the fact that linear electron flow (LEF) (and associated proton flux) is decreased upon Pi depletion. In one model, an imbalance of ATP or NADPH activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
106
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(114 citation statements)
references
References 47 publications
8
106
0
Order By: Relevance
“…There is also evidence that decreased ATP synthesis itself results in decreased ATP levels, slowing RuBP regeneration, which in turn limits Rubisco and PSII activity. These results are consistent with regulation via stromal P i , as previously proposed Sharkey 1990;Kanazawa and Kramer 2002;Takizawa et al 2008), or alternatively by an allosteric regulator of ATP synthase, which responds similarly. In this way, the ATP synthase may act as a central co-regulator of the light and dark reactions of photosynthesis.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…There is also evidence that decreased ATP synthesis itself results in decreased ATP levels, slowing RuBP regeneration, which in turn limits Rubisco and PSII activity. These results are consistent with regulation via stromal P i , as previously proposed Sharkey 1990;Kanazawa and Kramer 2002;Takizawa et al 2008), or alternatively by an allosteric regulator of ATP synthase, which responds similarly. In this way, the ATP synthase may act as a central co-regulator of the light and dark reactions of photosynthesis.…”
Section: Discussionsupporting
confidence: 80%
“…The linear relationships seen in Figs 4b, c and 7b show that the likely path of feedback control is as predicted earlier Sharkey 1990;Takizawa et al 2008): metabolic events lead to the slowing of the ATP synthase, leading to acidification of the lumen pH and subsequent slowing of LEF at the cyt b 6 f complex. The same lumen acidification also activates the q E response (Fig.…”
Section: Downregulation Of the Atp Synthase Under Feedbacklimiting Comentioning
confidence: 63%
See 1 more Smart Citation
“…It has been suggested that if such an activity sequesters stromal Pi below the K m of the thylakoid ATP synthase, the resulting decrease in proton conductivity could serve as a means of down regulating photosynthetic light capture. 4,38 The PHT4;1 promoter also exhibited weak activity in the root stele (Fig. 1g), which corroborates previous results indicating that endogenous transcripts are present in roots at low levels.…”
Section: Discussionsupporting
confidence: 79%
“…We found that reductions in ATP synthase content increased NPQ and probably the transthylakoid DpH as previously reported (Price et al, 1995). It has also been suggested that ATP synthase senses the status of stromal metabolites either directly or indirectly (Kramer et al, 2004) and it has been suggested that its activity can be modulated by altering Pi levels (Kanazawa and Kramer, 2002;Takizawa et al, 2008). A number of Calvin cycle enzyme activities are regulated by the chloroplast ferredoxin-thioredoxin pathway (e.g.…”
Section: Atp Synthase Activity Varies In Vivosupporting
confidence: 59%